СПЕЦІАЛЬНІСТЬ „КЛАСИЧНА ФІЛОЛОГІЯ” У ЧЕРНІВЕЦЬКОМУ УНІВЕРСИТЕТІ ЗА РУМУНСЬКОГО ПЕРІОДУ - Chakal (Makar), Inesa (Casa Cărţii de Ştiinţă, 2015)
In the article an attempt to research some aspects of professors’ and scientists’ activity of Chernivtsi university functioning in the Romanian period is done, which created and developed classical philology, provided its teaching (Radu Sbiera, Dimitrie Marmelyuk, Karol' Sigel', Teofil Sauchuk-Sevyanu, Orest Luciy, Vasile Greku etc.). Speciality „Classical philology” offered study of basic Latin and Greek languages and literatures in the context of whole ancient civilization. For our research „Annuals of the Chernivtsi university” which were published in 30th years of the ХХ century served as sources, contained general information about activity of all structures of educational institution.
Speciality “Classical Philology” at Chernivtsi University in the Romanian Period
Keywords: Класична філологія; Чернівецький університет; румунський період; Раду Сбієра; Дімітріє Мармелюк; Теофіл Саучук-Севяну; Васіле Греку; Кароль Сігель; Vasile Grecu; Theofil Sauciuc-Săveanu; Dimitrie Marmeliuc; Radu Sbiera